Urgensi Etika Profesi Hakim dalam Pandangan Hukum Islam sebagai Upaya Penegakan Keadilan di Indonesia - Muhamad Raka Putra Satriya; Muhamad Junaidi (Lembaga Yasin AlSys, 2025)
Judicial ethics as articulated in the Code of Ethics and Guidelines for Judges’ Conduct (KEPPH) is a fundamental instrument designed to safeguard the independence, integrity, and objectivity of the judiciary in Indonesia, particularly amid disparities in judicial decisions and the exposure of ethical violations by some judges, which highlight the urgency of strengthening ethical instruments as the moral safeguard of the courts. This study aims to analyze the legal status of KEPPH within the national legal system and its relevance to the principle of justice as the ultimate objective of law. Methodologically, it adopts a normative juridical approach based on library research by examining legislation, KEPPH, relevant judicial decisions, as well as positive law literature and pertinent references on Islamic legal ethics. The analysis is conducted using a normative qualitative method to map the ratio legis and scope of regulation, test the consistency of implementation, and assess the effectiveness of ethical oversight mechanisms. The findings indicate that KEPPH is not merely a technical code but a manifestation of the values of justice, honesty, impartiality, and accountability that must permeate every stage of the adjudication process, and therefore needs to be reinforced through the standardization of principle interpretation, the enhancement of judges’ ethical capacity through continuous training, and the optimization of discipline enforcement based on transparency and public participation. These measures are expected to enable KEPPH to function as a form of living ethics that promotes consistency in judgments, reduces opportunities for misconduct, and restores public trust in the judiciary as the guardian of constitutional justice. Theoretically, this study sharpens the conceptual understanding of the relationship between codes of ethics and judicial authority, while practically it provides an evaluative framework for the Supreme Court (Mahkamah Agung) and the Judicial Commission (Komisi Yudisial) in formulating more implementable guidelines. The policy implications include integrating ethical performance indicators into promotion, rotation, and professional development processes, as well as utilizing easily accessible technology for reporting violations, thereby underscoring the urgency of sustained public accountability.